Yeast surface displayed xylanase is an efficient strategy to induce corn defence response. Issue 1 (1st January 2020) - Liang, Hailong; Wang, Qing; Shen, Shen; Jia, Yanrong; Li, Pan; Zeng, Fanli; Hao, Zhimin; Dong, Jingao
Abstract: As a valuable and powerful platform technology, yeast surface display (YSD) has been widely used in various biotechnological fields, but little in agricultural applications. Xylanase can be used as an elicitor in the plant–pathogen interaction system and induce corn defence response. In this study, the YSD technology was used to express the xylanase protein family from Setosphaeria turcica, which is a novel strategy for plant protection. First, five genes encoding xylanase were selected from the S. turcica genome database. The conserved domains of these genes were analyzed, which revealed that these genes were highly conserved. Here, we selected two of the five genes and expressed them by a prokaryotic expression system, but the two xylanase genes were expressed in inclusion bodies and showed no activity. To make them available in the application, we successfully constructed them in a YSD system. The products were detected for enzyme activities and the activities of two xylanases were 16.72 and 19.12 U/mL, respectively. We finally proved that the yeast-displaying xylanase was an efficient strategy to induce corn defence response, as four defence genes in corn, PR-1, PR-4, SOD and CAT were induced after treatment with the yeast displaying xylanases.